Hispanic Preschoolers Intake of Sugary Drinks: Interactions Between Mothers and Fathers Feeding Practices (OR03-04-19) - Lora, Karina (Curr Dev Nutr, 2019)
OBJECTIVES: To 1) assess the relationship of home availability of sugary drinks (SD), mothers’ feeding practices, and fathers’ practices related to promoting their children's intake of SD (fathers’ SD practices) with children's intake of SD and 2) evaluate whether fathers’ SD practices moderated the relationship between mothers’ feeding practices and children's intake of SD. METHODS: Hispanic mothers (n = 202) of 2-to-5-year-old children reported home availability of sugary drinks, their feeding practices (i.e., monitoring, restriction, food for emotion regulation), their children's fathers’ SD practices (i.e., frequency of bringing SD to the home, using SD for emotion regulation) and children's intake of SD. Availability of SD was dichotomized as low (never/rarely/sometimes) and high (frequently/always) availability. Fathers’ feeding practices were dichotomized as low (never/once per month/once per week) and high frequency (2-3 days per week/4-6 days per week/everyday). Linear regression models tested the multivariable association between child's intake of SD and variables of interest, and interaction terms were tested for moderation effects. RESULTS: Home availability of SD, fathers drinking SD in front of the child, and fathers using SD for emotion regulation were associated with children's SD intake (P < 0.05). Fathers’ use of SD for emotion regulation moderated the association of mothers’ restriction and child's SD intake (P < 0.04). Fathers’ use of SD for emotion regulation moderated the association of mothers monitoring and child's SD intake (P < 0.02). When fathers used SD for emotion regulation at high frequencies, mothers’ restriction and monitoring practices reduced child's SD intake (P = 0.07 and 0.01, respectively). However, when fathers used SD for emotion regulation at low frequencies, there was no longer a relationship between mothers’ restriction and monitoring practices and child's SD intake (P = 0.30 and 0.95, respectively). CONCLUSIONS: Mothers’ restriction and monitoring practices appear to weaken the influence of fathers use of SD in response to children's emotions and intake of SD. The moderating effect of mothers or fathers feeding behaviors on each other's behaviors warrants future investigation. FUNDING SOURCES: U54GM104938.